Long-term results of office-based pneumatic retinopexy using pure air. Issue 12 (6th September 2011) - Yee, Kenneth M P; Sebag, J
Abstract : Aims: The long-term results of office-based pneumatic retinopexy (PR) using only filtered air were evaluated in a case series of rhegmatogenous retinal detachments with more than 3 years of follow-up, on average. Methods: 77 cases of primary rhegmatogenous retinal detachments arising from superior tears (mean=1.6 tears) were treated with cryopexy (n=61) or laser (next day, n=16) and intravitreal injection of pure air in an office setting. The macula was detached preoperatively in 37 eyes (48.1%). Outcome measures were single-operation success, final reattachment rates and visual acuity (VA). Results: Subjects were followed for 6–186 months (mean follow-up = 40.7 months, 46.8% ≥2 years, 25% ≥5 years). In all cases, the air bubble was gone within 5 days. Single-operation success was achieved in 62/77 (80.5%) eyes. Repeat PR was successful in four cases, increasing the PR reattachment rate to 85.7%. Scleral buckle was performed on the remaining 11 eyes (14.3%), 1 with vitrectomy. The final reattachment rate was 100%. VA improved ≥2 Snellen lines in 53.2% of patients, with 50/77 (64.9%) attaining VA ≥20/40. Following PR, 87% of subjects had the same or better VA. Conclusions: Office-based pure-air PR achieves acceptable reattachment rates with good visual outcomes and long-term efficacy. Eliminating the need for expansile gases makes this approach more widely available, decreases recovery time and lowers healthcare costs.